Gender differences in brain activity underlying acupuncture sensations at LR3: a task-based fMRI study - Chu, Hao; Jiang, Bin-Jian; Li, Dong-Na; Duan, Wen-Xiu; Gao, Zi-Zhan; Yang, Yan-Yan; Dai, Ning; Xu, Chun-Sheng; Wu, Zi-Jian (Frontiers in Human Neuroscience, 2025)
BackgroundAcupuncture has been practiced in China for centuries, and LR3 (Taichong) is a key acupoint of the liver meridian that has been widely studied. Whether its central mechanism differs by sex remains unclear, because earlier work used single-sex or mixed-sex samples without stratified analysis. To close this gap, we used task-based fMRI together with the Massachusetts Acupuncture Sensation Scale to compare sex differences in brain activation and thalamic functional connectivity.MethodsWe enrolled 30 men and 25 women in a block-design acupuncture task, the modular task-based functional magnetic resonance imaging (fMRI) technique was employed to investigate brain activity, and the Massachusetts Acupuncture Sensation Scale (MASS) was utilized to assess acupuncture sensations experienced by the participants. Alterations in activated brain regions and functional connectivity were examined separately for males and females. Statistical analyses were performed to determine potential gender differences in acupuncture sensation.ResultsSignificant statistical differences were observed in the 12 acupuncture sensation scores of the MASS scale (p < 0.001). Acupuncture LR3 activated the left inferior cerebellar gyrus, right superior margin gyrus, and left posterior central gyrus in women, and activated the right superior margin gyrus, left central sulcus, and right paracentral lobule in men. Enhanced functional connectivity was also observed in the bilateral thalamus of women: the bilateral caudate nucleus, right precuneus, right cuneate fissure, and bilateral lingular gyrus were highly active. Furthermore, the right thalami also demonstrated enhanced functional connectivity with the left cuneate fissure, right posterior cingulate gyrua, and left precuneu.ConclusionThe differences in the functional connectivity of the right superior marginal gyrus and thalamus between men and women may account for the differences in acupuncture sensory processing between men and women. In addition, the right superior marginal gyrus may be a specific brain region critical for activation of the LR3 acupoint.